منهجية المقاصد والوسائل في الاجتهاد الفقهي - معتز الخطيب (International Institute of Islamic Thought, 2013)
خلَص البحث إلى أنَّ "الوسائل" تصلُح أن تُصاغَ في نظرية يمكن أن تسمى "نظرية الوسائل"، وأنَّ التمييز بين المقاصد الثابتة والوسائل المتغيرة يَصلُح أن ينتصب منهجيةً صالحةً للاجتهاد الفقهي، بحيث يفرّق بين الثابت والمتغير من الوسائل حتى لا يتم الجمود على المنصوص، بدافع تَوَهم التعبد في كلِّه، وقد عالج البحث ثلاثة محاور: المفاهيم، وتاريخ المنهجية في العقل الفقهي، وأبعاد المنهجية المقترحة. The study discusses how the "means" may be articulated in a theory named "Theory of the Means". Distinguishing between the permanent objectives (maqasid) and changing means offers a legitimate methodology for jurisprudential ijtihad, which leads to a differentiation between the time-constant intent of this Law and the changing means. This methodology circumvents rigidity of scriptural texts under the illusion that texts are only rites for worship. The study addresses three themes: concepts; the history of methodology in the jurisprudential mind; and the dimensions and implications of the suggested methodology.